Compounds Profile of Polar Subfraction of Ethyl Acetate Fraction of Soft Coral Nepthea sp., Antioxidant and Cytotoxic Properties - Baru Sadarun; Adryan Fristiohady; Nur Syifa Rahmatika; Agung Wibawa Mahatva Yodha; Muhammad Hajrul Malaka; Andini Sundowo; I. Sahidin (Future Science)
Nepthea sp., a soft coral In Indonesia's South-East Sulawesi, it thrives. The chemical and pharmacological properties of this genus have not been studied in this location. As a result, the goal of this page is to offer a broad overview of both properties of Nepthea sp. The sample was taken from Hoga Island. Methanol was used to extract the material, which was then fractionated with hexane and ethyl acetate to produce n-hexane, ethyl acetate, and methanol fractions. Vacuum liquid chromatography was also used to fractionate the ethyl acetate fraction. Phytochemical screening, LC-MS/MS, Total Phenolics Content (TPC), and Total Flavonoids Content (TFC) were used to determine the chemical contents. DPPH radicals and ABTS were used to assess antioxidant activity and MTT assays for cytotoxicity. Six subfractions are produced by fractioning the ethyl acetate fraction (160 g), with the most polar subfraction (F) weighing 15.4 g. The phenolics and flavonoids constituents in Subfraction F have IC50 values of 68.77±4.8 mg GAE/g extract and 0.22±0.1 mgQE/g extract, respectively. The presence of phenolics, flavonoids, and alkaloids in the subfraction F is supported by the LC-MS/MS data, Subfraction F has 3-ter-butyl-4-methoxyphenol (terpenoids or phenolics compound), isosalsoline (alkaloids), valine (amin acid), and several unidentified chemicals with molecular formulas C15H23NO3, C33H47NO4, C29H49NO3 (alkaloids or amino acid) and C8H18O3 (phenolic compound).The IC50 values (mg/L) of 101.1 ± 8.8 (DPPH) and 89.76 ± 7.5 (ABTS) indicate that F has antioxidant capacity, and it is also cytotoxic against breast cancer cell lines (MCF-7) with an IC50 of 170.72±6.5mg/mL.